Variable Herz estimates for fractional integral operators - Heraiz , R. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.5In this paper, the author study the boundedness of fractional integral operators on a variable Herz-type Hardy space $HK^{α (· )}_{p(· ),q(· )}(\mathbb{R}^n)$ by using the atomic decomposition.